Bacteriological analysis of seawater from San Salvador in Belen bay areas in Banate Bay, Banate - Abancio, Cely Ann Lim (2000.)
This study was conducted at Banate bay, Banate from a point from Belen to San Salvador. Two samplings were taken one week apart and was analyzed for the Most Probable Number (MPN) per ml coliform count. The Multiple fermentation tube technique showed that in Poblacion approximately 100 meters from the shore had the lowest MPN values for both samplings which was >3 MPN per ml. The highest count of greater than or equal to 2400 MPN per ml was obtained in sites Belen-10, Belen-50, and Bularan-10 meters away from the shore. As the distance from the shore increases, the MPN values usually decreases, showing that the area near the shore would exhibit high coliform counts than the area further away from the shore. The tide and the weather may have affected the coliform counts because of the differences of MPN values.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Seawater -- Bacteriological analysis -- Banate